2011
DOI: 10.1007/s10661-011-2085-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of trace elements in different tissues of three commonly available fish species regarding their gender, gonadosomatic index, and condition factor in a wetland ecosystem

Abstract: In the present research, accumulation of Cd, Co, Cr, Cu, Mn, Ni, Pb, V, and Zn were determined in sediments and fillet, liver, kidney, gonads, and gills of three commonly fish species in the largest wetland ecosystem that is located in southwest of Iran; Shadegan wetland. Shadegan is one of the most important wetland that posses various fauna and flora but suffers inputs from agricultural and industrial activities. So, sediment samples and fish species including Barbus grypus, Barbus sharpeyi, and Cyprinus car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The only exceptions were Mg and Co in S. glanis, which showed negative relationships, suggesting that life-history changes may play a considerable role. Previous literature showed, however, that this relationship can be highly variable (Alhashemi et al 2012;Luczynska et al 2016;Dragun et al 2016;Rakocevic et al 2018). One possible explanation is that fish could have physiological mechanisms that reduce the impact of metals on body condition (Tenji et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only exceptions were Mg and Co in S. glanis, which showed negative relationships, suggesting that life-history changes may play a considerable role. Previous literature showed, however, that this relationship can be highly variable (Alhashemi et al 2012;Luczynska et al 2016;Dragun et al 2016;Rakocevic et al 2018). One possible explanation is that fish could have physiological mechanisms that reduce the impact of metals on body condition (Tenji et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Metal and metalloid (hereafter "metal") pollution is one of the most serious environmental hazards (Gall et al 2015;Yang et al 2018), posing both ecological and human health risks (Alhashemi et al 2012;Liu et al 2018Liu et al , 2021. This threat originates from their uptake from the environment and subsequent bioaccumulation in animal tissues over time and their tendency to biomagnify through the transfer along the food chain to higher trophic positions (Markert et al 2003;Madgett et al 2021;Yang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, some of the pollutants are persistent due to their non-biodegradability and long biological half-life, e.g., heavy metals [[21], [22], [23]]. The distribution of heavy metals in water, sediments, and fish plays a key role in forming sources of heavy metal pollution in the aquatic ecosystem [24,25]. Pollution from domestic and industrial wastes is high at Kanpur and Allahabad, and Varanasi.…”
Section: Introductionmentioning
confidence: 99%
“…Through a study done with Barbus grypus, Barbus sharpeyi and Cyprinus carpio, Alhashemi et al (2012) concluded that sex is an important factor and that it can interfere with the bioaccumulation of metals in sh. In B. grypus and B. sharpeyi, a greater bioaccumulation of metals was observed in females when compared to males.…”
Section: Concentration Of Metals In the Gonadsmentioning
confidence: 99%